Rapid Activation of ATR by Ionizing Radiation Requires ATM and Mre11 - Myers, Jeremy S. (2006)
The ataxia-telangiectasia mutated (ATM) 1 and ATM- and Rad3-related (ATR) protein kinases are crucial regulatory proteins in genotoxic stress response pathways that pause the cell cycle to permit DNA repair. Here we show that Chk1 phosphorylation in response to hydroxyurea (HU) and ultraviolet radiation (UV) is ATR-dependent and ATM- and Mre11-independent. In contrast, Chk1 phosphorylation in response to ionizing radiation (IR) is dependent on ATR, ATM, and Mre11. The ATR and ATM/Mre11 pathways are generally thought to be separate with ATM activation occurring early and ATR activation occurring as a late response to double strand breaks. However, we demonstrate that ATR is activated rapidly by IR, and ATM and Mre11 enhance ATR signaling. ATR-ATRIP recruitment to double-strand breaks is less efficient in the absence of ATM and Mre11. Furthermore, IR-induced replication protein A (RPA) foci formation is defective in ATM and Mre11 deficient cells. Thus, ATM and Mre11 may stimulate the ATR signaling pathway by converting DNA damage generated by IR into structures that recruit and activate ATR.